2016
DOI: 10.1007/s00421-016-3459-y
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of heart rate recovery and vagal rebound after exercise

Abstract: PurposeThe prognostic power of heart rate recovery (HRR) after exercise has been well established but the exact origin of individual differences in HRR remains unclear. This study aims to estimate the heritability of HRR and vagal rebound after maximal exercise in adolescents. Furthermore, the role of voluntary regular exercise behavior (EB) in HRR and vagal rebound is tested.Methods491 healthy adolescent twins and their siblings were recruited for maximal exercise testing, followed by a standardized cooldown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The dynamic HR response to exercise may have a genetic basis. Moderate heritability (32–34%) has been demonstrated for exercise and recovery HR during sub-maximal treadmill test [ 43 , 44 ], while a more recent tween study found higher heritability (65%) for HR recovery after one minute from exhaustion in healthy adolescents [ 18 ]. Recent studies have characterized the genetic contribution to resting HR [ 45 ] and HR variability [ 46 ] and their interaction with mortality, but direct link between HR response to exercise and specific genes has not yet been found.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic HR response to exercise may have a genetic basis. Moderate heritability (32–34%) has been demonstrated for exercise and recovery HR during sub-maximal treadmill test [ 43 , 44 ], while a more recent tween study found higher heritability (65%) for HR recovery after one minute from exhaustion in healthy adolescents [ 18 ]. Recent studies have characterized the genetic contribution to resting HR [ 45 ] and HR variability [ 46 ] and their interaction with mortality, but direct link between HR response to exercise and specific genes has not yet been found.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to reactivity, recovery plays a crucial role regarding the adaptability of the organism, to face an event and then return to resting level ( Stanley et al, 2013 ). Vagal recovery has also been termed “vagal rebound” in the literature ( Nederend et al, 2016 ). Following our metaphor, recovery deals with whether individuals fill their tank quickly enough to face another stressor, in order to have enough ability to self-regulate and react effectively.…”
Section: Cardiac Vagal Control: a Physiological Indicator Of Self-regmentioning
confidence: 99%
“…The median age at the EST without AAD was 36 years (IQR, 19-47). Sixty-eight patients (36%) were symptomatic before diagnosis: 52 patients (76%) had an arrhythmic syncope and 16 patients (24%) an ACA as their worst symptom before diagnosis (median age at worst symptom, 14 years [IQR, [11][12][13][14][15][16][17][18][19][20]). Symptomatic patients were more often the familial proband (49% versus 8%; P<0.001) and were younger at the EST (23…”
Section: Study Populationmentioning
confidence: 99%